A History of Spike-Timing-Dependent Plasticity - Markram, Henry; Gerstner, Wulfram; Sjöström, Per Jesper (Frontiers in Synaptic Neuroscience, 2011)
How learning and memory is achieved in the brain is a central question in neuroscience research. Key to today’s research into information storage in the brain is the concept of synaptic plasticity, a notion that has been heavily influenced by Donald Hebb’s 1949 postulate. Hebb conjectured that repeatedly and persistently coactive cells should increase connective strength among populations of interconnected neurons as a means of storing a memory trace, also known as an engram. Hebb certainly was not the first to make such a conjecture, as we show in this history. Nevertheless, literally thousands of studies into the classical frequency-dependent paradigm of cellular learning rules were directly inspired by the Hebbian postulate. But in more recent years, a novel concept in cellular learning has emerged, where temporal order instead of frequency is emphasized. This new learning paradigm — known as Spike-Timing-Dependent Plasticity, or STDP — has rapidly gained tremendous interest, perhaps because of its combination of elegant simplicity, biological plausibility, and computational power. But what are the roots of today’s STDP concept? Here, we discuss several centuries of diverse thinking, beginning with philosophers such as Aristotle, Locke and Ribot, traversing e.g. Lugaro’s plasticità and Rosenblatt’s Perceptron, and culminating with the discovery of STDP. We highlight interactions between theoretical and experimental fields, showing how discoveries sometimes occurred in parallel, seemingly without much knowledge of the other field, and sometimes via concrete back-and-forth communication. We point out where the future directions may lie, which includes interneuron STDP, the functional impact of STDP, its mechanisms and its neuromodulatory regulation, and the linking of STDP to the developmental formation and continuous plasticity of neuronal networks.